Factors Contributing to the Increasing Threat of Striga hermonthica to Farming Communities in Western Kenya - Evans A. Atera; Mayumi Kikuta; Joseph Bosire; Yuichiro Tsuchiya; Daigo Makihara (International Journal of Agronomy)
Striga hermonthica remains a major biological constraint to food production in sub-Saharan Africa. This study investigates the critical paradox underlying its persistent threat in western Kenya: Despite decades of research and the availability of numerous control measures, Striga infestation continues to expand. A field survey was conducted across twelve administrative units over three years (2019, 2022, and 2023), involving 174 farming households to assess their knowledge, practices, and the multifaceted factors contributing to the problem. Our findings reveal that while a majority of farmers are aware of and practice Striga control, infestation remains severe (69% of fields) and results in estimated maize yield losses of 47%. We identified key drivers perpetuating this gap between intervention and on-the-ground reality, including the continuous cultivation of susceptible staple crops driven by subsistence needs and evidence of Striga’s ecological expansion into new niches, such as higher altitudes. We conclude that the failure to control Striga is not merely a technical issue, but a systemic problem rooted in a combination of ecological and socioeconomic barriers. Our study highlights the need for a holistic approach that moves beyond agronomic techniques to inform the development of more effective and sustainable management strategies that address these underlying constraints.